2012
DOI: 10.1166/jnn.2012.6442
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Accumulation and Release of Nanosilica During Irradiation of Polymer Nanocomposites by Ultraviolet Light

Abstract: Polymer nanocomposites are increasingly used in applications that are subjected to harsh environments. Owing to polymer's susceptibility to photodegradation, nanofillers in a polymer nanocomposite may be released into the environments during the composite's life cycle. Such release potentially poses an environmental health and safety problem and may hinder commercialization of these advanced materials. This study investigated the fate and release of nanosilica from epoxy/nanosilica composites. Specially-design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
2
41
2
Order By: Relevance
“…Coating the particles would occupy these "defect sites" and inhibit the reduction of TiO 2 by UV light and, consequently, prevent some destruction of the polymer binder (Allen et al, 2004;Petersen et al, 2014). Exposure of nano-doped polymers to UV light was studied by Nguyen et al (2012), where amine-cured epoxies doped with either SiO 2 NP or MWCNT exposed to realistic environmental conditions (50°C, 75% relative humidity) showed variable mass losses created by photooxidative chain scission. The same behavior was observed with other polymer composites (see Najafi and Shin for instance (Najafi and Shin, 2005)).…”
Section: Plastics and Polymersmentioning
confidence: 99%
“…Coating the particles would occupy these "defect sites" and inhibit the reduction of TiO 2 by UV light and, consequently, prevent some destruction of the polymer binder (Allen et al, 2004;Petersen et al, 2014). Exposure of nano-doped polymers to UV light was studied by Nguyen et al (2012), where amine-cured epoxies doped with either SiO 2 NP or MWCNT exposed to realistic environmental conditions (50°C, 75% relative humidity) showed variable mass losses created by photooxidative chain scission. The same behavior was observed with other polymer composites (see Najafi and Shin for instance (Najafi and Shin, 2005)).…”
Section: Plastics and Polymersmentioning
confidence: 99%
“…Nanomaterial accumulation at the nanocoating surface is a common observation from the polymer nanocoating degradation processes [15][16][17][18][19]. The primary objective of this SP is to provide a specific protocol for collecting and quantifying the amount of nanomaterial that is released after a combination of accelerated weathering and simulated rain spray.…”
Section: Principles and Scopementioning
confidence: 99%
“…To ascertain whether this was the case, they analyzed particles collected at the bottom of the sample holder and found evidence of free silica nanoparticles in the case of the silica/epoxy material but no evidence of free MWCNTs in the case of MWCNT/epoxy. [36][37] The authors suggested that MWCNTs, being long, fibrous 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Draft 09-11-14 30 materials, form entangled networks on the PNC surface as the host matrix photodecomposes, which precludes their easy gravitational dropping off of the vertically aligned PNC. Spherical silica particles cannot entangle and easily fall off the surface as they become exposed, although the researchers did not determine whether the free nanofillers were aggregated with remnants of the host materials.…”
Section: Release Of Enms Due To Photochemical Degradation Of Thementioning
confidence: 99%
“…Free silica particles passively fell off the exposed surface. [36][37] Titania Direct coating on wood, PET, and tile UV weathering with agitation Air N/A UV light increased the number of released particles due to weakening of the particle-substrate interactions. Visible light showed no effect.…”
Section: Air Nomentioning
confidence: 99%